Novel strategies for inhibiting cancer growth - Schaefer, Rainer (Curtin University, 2008)
At present, most cancers are treated with surgery, radiotherapy and chemotherapy, used alone or in combination. Surgery and radiotherapy are the primary treatment modalities after early detection of cancers and they significantly increase the patient survival time. However, the value of cytotoxic chemotherapy has recently been questioned (Morgan, Ward and Barton 2004. Clinical Oncology 16: 549-560) as it became apparent that single cytotoxic chemotherapy barely contributes to the five-year survival rate in cancer. However, different chemotherapeutic strategies may be combined improving their efficacy dramatically.In this study, ninety two different compounds having anti-cancer potential were tested in various combinations against four human cancer cell lines (MCF-7 breast; HepG2 liver; Caco-2 colon and JU77 mesothelioma) in an attempt to find compounds that effectively eradicate cancer cell lines within a therapeutic range. The cancer cell lines have been chosen to illustrate the diversity in cancer cell signaling. The diversity of the signalling patterns in different cancer cell lines becomes apparent when monitoring the viability of these cell lines during different chemotherapeutic treatments. Several potent combinations of narrow and broad-spectrum inhibitors were discovered that combined well in killing cell lines. Most of these combinations were specific against single cell lines. For example, PD98058, LY294002, bromocriptine and 120nM staurosporine promoted cell death in JU77 mesothelioma cells, but this combination was not fully effective in killing MCF-7 cells. On the other hand, bromocriptine or oxytocin and 120nM staurosporine effectively killed MCF-7 cells but not JU77 cells. However, some combinations worked effectively to kill multiple cell lines. Two such examples include geftinib and 120nM staurosporine or selenomethionine and selenite.Broad-spectrum inhibitors alone effectively killed cell populations, but at concentrations too high to be applied in vivo, due to their toxicity. However, the concentration of the broad-spectrum inhibitors needed in the combinations, to ensure eradication of a cell line, could be substantially reduced (in some cases by several orders of magnitude) by using appropriate combinations of narrow-spectrum inhibitors. For example, 6μM staurosporine alone was required to kill JU77 cells. However, 6nM staurosporine was effective in killing JU77 cells when combined with PD98058, LY294002 and rapamycin. Other successful combinations included: 1. vitamin C, suramin and letrozole; 2. flavine adenine nucleotide or selenotrisulphides and β-lapachone; 3. a most promising combination, because of its potency and bioavailability, was selenite combined with selenomethionine and lithium chloride.Whilst the culture system using banks of cancer cell lines can be a useful tool for selecting effective cytotoxic compounds and their combinations, its translation to effective in vivo strategies is limited. In most such studies fetal calf serum is included as a growth supplement for cells in culture. However, this study demonstrates that the inclusion of adult human albumin is also important as the adsorption of compounds to it differ significantly to fetal albumin (Brodersen and Honore 1989 Acta Paediatr.Scand. May, 78(3): 342-6). However, of the combinations reported above combination 2. and 3. remained effective in adult human albumin within a therapeutic range.A tumour model was then established by injecting JU77 mesothelioma cells into nude balb/c mice. JU77 cells are a “non-tumourigenic” human cell line. However, the cells became “tumourigenic” when insulin-like growth factor- 1 was also co-injected on a daily basis. In this manner, a subcutaneous tumour of JU77 mesothelioma cells rapidly grew approaching maximum size over nine days. Nude balb/c mice bearing JU77 tumours were treated with selenite, selenomethionine and lithium chloride combination while supplementing insulin-like growth factor 1 continuously. Tumours rapidly decreased in size and became invisible after five days. In contrast, tumours treated with carrier and insulin-like growth factor 1 continued to grow. Low side effects of the treatment with the selenite combination were observed. The most notable observation was a moderate loss in weight of the mice, only following the first day of treatment. The inclusion of insulin-like growth factor 1 to maintain the tumours altered some of the haematological and biochemical parameters but the selenite combination did not further change these parameters. The histology of the tumours illustrated thick, closely packed layers of malignant cells that surrounded a central necrosis and rapidly decreased in thickness as the selenite combination was applied leaving behind a few clusters of necrotic cells and an inflammatory infiltration. In normal tissues, only a few abnormalities were discovered mainly due to the inherited defect of the nude mice. These abnormalities were exaggerated by treatment with insulin-like growth factor 1 but did not further change with the selenite combination. These results indicated that the selenite combination affected the tumour tissues highly selective with little side effects to the normal tissues.In future, it will be interesting to know whether this compound combination is similar effective for tumours that grow without supplementation of insulin-like growth factor-1. In other tumour models, similar high concentrations of insulin-like growth factor-1 have been reported without supplementation due to existing “autocrine loops” and this might be a reason why the immune responses in these models is also disabled against aberrant cancerous signalling. This interesting new aspect which focuses on the endocrine response due to aberrant cancerous signaling is a promising path for inhibiting cancer growth.